Role of Fc Gamma Receptors in Triggering Host Cell Activation and Cytokine Release by Borrelia burgdorferi - Talkington, Jeffrey (American Society for Microbiology, 2001)
Borrelia burgdorferi, the spirochetal bacterium that causes human Lyme disease, encodes numerous lipoproteins which have the capacity to trigger the release of proinflammatory cytokines from a variety of host cell types, and it is generally believed that these cytokines contribute to the disease process in vivo. We previously reported that low-passage-number infectious B. burgdorferi spirochetes express a novel lipidation-independent activity which induces secretion of the proinflammatory cytokine tumor necrosis factor alpha (TNF-α) by the mouse MC/9 mast cell line. Using RNase protection assays, we determined that mast cells exposed in vitro to low-passage-number, but not high-passage-number, B. burgdorferi spirochetes show increased expression of additional mRNAs representing several chemokines, including macrophage-inflammatory protein 1α (MIP-1α), MIP-1β, and TCA3, as well as the proinflammatory cytokine interleukin-6. Furthermore, mast cell TNF-α secretion can be inhibited by the phosphatidylinositol 3-kinase inhibitor wortmannin and also by preincubation with purified mouse immunoglobulin G1 (IgG1) and IgG2a, but not mouse IgG3, and by a mouse Fc gamma receptor II and III (FcγRII/III)-specific rat monoclonal antibody, suggesting the likely involvement of host FcγRIII in B. burgdorferi-mediated signaling. A role for passively adsorbed rabbit or bovine IgG or serum components in B. burgdorferi-mediated FcγR signaling was excluded in control experiments. These studies confirm that low-passage-number B. burgdorferi spirochetes express a novel activity which upregulates the expression of a variety of host cell chemokine and cytokine genes, and they also establish a novel antibody-independent role for FcγRs in transduction of activation signals by bacterial products.